Investigation on the characterization and modelling of Fracture Process Zone behavior in Concrete Beams subjected to Three-Point Loading Tests - H. S. Vishwanatha; S. Muralidhara; B. K. Raghu Prasad (Fracture and Structural Integrity)
The fracture behavior of quasi-brittle materials such as concrete is characterized by the presence of a fracture process zone (FPZ) that precedes the main crack. Within this zone, various mechanisms, including the formation of microcracks, crack deflection, aggregate interlocking, and crack branching, contribute to the complex nature of the fracture behavior. Traditional experimental methods and other techniques often face challenges in fully capturing the micromechanical mechanisms occurring in the fracture process. To address this challenge, numerical models have been developed in the present study to investigate the evolution mechanisms of the FPZ. These models serve as valuable tools for simulating and analyzing the intricate behavior occurring at the microstructural level during the fracture process. By complementing experimental observations, these numerical approaches provide deeper insights into the fracture behavior of quasi-brittle materials and enhance the understanding of material failure. The outcome of present investigation clearly provides the evaluation method of FPZ in concrete beams of different sizes.